Using full rainfall rate distribution for rain attenuation predictions over terrestrial microwave links in Malaysia - Abdulrahman, A Y; Abdul Rahman, Tharek; Olufeagba, B J; Islam, Md Rafiqul (Science and Engineering Publishing Company, 2013)
The use of full rainfall rate distribution for the prediction of rain attenuation over terrestrial microwave links in Malaysia is presented in this letter. The experimental data consist of four-year measured rainfall rates and one-year rain attenuation measurements over six geographically spread DIGI MINI-LINKs operating at 15 GHz. The test results show that ITU-R model does not perform well for rain attenuation predictions in tropical Malaysian climate.